Validation of the Chinese Version of the Stigma Scale of Epilepsy - Wu, Yuanxia; Huang, Kailing; Wen, Shirui; Xiao, Bo; Feng, Li (Frontiers in Neurology, 2022)
Purpose: This study was carried out to test the validity and reliability of the Chinese version of the Stigma Scale of Epilepsy (SSE), with aim to better understand the public stigmatizing attitudes of epilepsy in China and help elucidate stigma determinants for interventions. Methods: The Stigma Scale of Epilepsy was translated into Simplified Chinese Mandarin. And most participants were enrolled via convenience sampling by randomly distributing questionnaires on the streets and parts of the participants were recruited by an online platform named Wenjuanxing. We assessed the psychometric properties of the SSE in 310 Chinese native-speaker. Cronbach's alpha was tested for reliability. Index of Content Validity (CVI) was calculated. Exploratory and confirmatory analysis were used to explore the factor structure and verify the validity of SSE. Results: The Cronbach's alpha is 0.936 for the overall scale. And the CVI value is greater than 0.78. The EFA extracted SSE six factors: the fear of seizure attacks (factor 1), sympathy for PWEs (factor 2); difficulties faced by PWEs (factor 3); speculation on PWEs’ feeling (factor 4); discrimination against PWEs (factor 5); knowledge about epilepsy (factor 6). The item 13 was proven to be problematic and has been eliminated. The CFA ensured the great construct validity (χ2/SD =1.725, GFI = 0.916, and RMSEA=0.048), convergent validity (the factor loads of each item corresponding to each latent variable＞0.6，AVE＞0.5, and CR＞0.7) and discrimination validity (All of the absolute value of correlation coefficient are＜0.5，and less than the square root of AVE) of the SSE. Conclusions: The Chinese version of the SSE scale was a valid and reliable tool to measure epilepsy-associated stigma in Chinese society.